How Does Job Insecurity Affect Workplace Harassment? The Interaction Effect of Hypercompetitive Attitude, Coworker Impression Management, and Leader Narcissism - Song, Geunhye (Frontiers in Psychology, 2021)
With concerns that artificial intelligence may replace existing jobs, job insecurity is becoming more prevalent. In-depth study of how job insecurity affects our society has become an important research topic. This study investigates the internal mechanisms through which such job insecurity influences workplace harassment. Based on the theories of psychological contract breach and the conservation of resources, this study proposes an indirect effect of job insecurity and a three-way moderation effect of hypercompetitive attitude, perceived coworker impression management, and leader narcissism on aggression intention. Using survey data from 286 employees in South Korea, bootstrapping analysis, hierarchical regression analysis, and a slope-difference test were performed to confirm the mediation and moderation effects. The results showed that hypercompetitive attitude mediates the association between job insecurity and aggression intention. The three-way interaction effect was also confirmed, such that the interaction effect of hypercompetitive attitude and coworker impression management is only effective when leader narcissism is high. This study contributes to the literature and business practices by offering significant suggestions to aid a more in-depth understanding of the workplace harassment occurrence process.